الإستراتيجية الإيرانية تجاه العراق بعد عام 2003 - علي حسين مجيد عبد (Tasnim International Journal for Human, Social and Legal Sciences, 2025)
can be said that Iran seeks to become a dominant regional power. As long as Iran has had its own regional project, particularly in Iraq, it has deemed the only way to achieve this goal to be through supporting federalism in Iraq after 2003, by supporting parties loyal to it in Iraq. Iranian Foreign Minister Manouchehr Mottaki stated that Iran would prefer to create a federal state in Iraq and not use Iraq as a base for an attack on Iran by the US military presence. However, it quickly realized that dividing Iraq could harm it, as the establishment of a Kurdish state in northern Iraq could increase separatist sentiment among Iranian Kurds, who represent 10% of Iran’s population. Therefore, it declared its rejection of dividing Iraq and instead favored the establishment of a weak Iraqi confederation based on religious and ethnic foundations, with Iran dominating southern Iraq. This is what Tehran has done through its strategy toward Iraq and its political and economic dominance of it through parties loyal to it.